The relationship between learning styles and motivation towards academic achievement among elementary school students - Yasin, Maizura; M. K. Raman Survey, Saraswathi (Human Resource Management Academic Research Society, 2024)
This study investigates the relationship between Semenyih Hulu Langat primary school students' learning styles and motivation for academic accomplishment. Totally, 152 participants, which a mix of boys and girls from various socioeconomic backgrounds, participated in this study. These respondents were selected from Sekolah Kebangsaan Bandar Sunway Semenyih, Selangor. This correlative research study aims to explore the relationship between learning style and motivation to achieve academic performance in core subjects by Level 2 students at Sekolah Kebangsaan Bandar Sunway Semenyih, Ulu Langat District. The questionnaire method was used in this research. All study variable information was collected during the occurrence of three learning style research domains: visual, auditory and kinesthetics learning styles. When studying two aspects of student motivation, it is focused on intrinsic and extrinsic categories. This study at Sekolah Kebangsaan Bandar Sunway Semenyih demonstrates a substantial correlation between learning style and learning desire among students in grades 4 and 5. The results of the study's analysis indicate a strong relationship between students' learning preferences and their academic achievement at Sekolah Kebangsaan Bandar Sunway Semenyih. Academic achievement in grades 4 and 5 at Sekolah Kebangsaan Bandar Sunway Semenyih did not significantly correlate with learning motivation, according to research. Every learner has a unique way of learning. The study's findings also demonstrate that pupils have two different learning preferences. Most students adjust their learning style to fit the subject matter they are studying.